Efektivitas Penggunaan Quizizz Dalam Meningkatkan Hasil Belajar Tajwid Mahasiswa Pendidikan Bahasa Arab Di UNM - Dessy Sintari Daoed; Susiawati Susiawati; Irfan Irfan; Mastur Mastur; Randy Randy (CV. SINAR HOWUHOWU, 2026)
This study aims to determine the use of the Quizizz application in Tajwid learning, the effectiveness of Quizizz in improving Tajwid learning outcomes, and the extent of the improvement in learning outcomes of Arabic Language Education students at UNM after using Quizizz. This research is motivated by the low interest and learning outcomes of students in Tajwid courses due to the use of conventional and less interactive learning methods. Therefore, technology-based learning media are needed to increase students’ motivation and engagement in the learning process. This study used a quantitative approach with an experimental method. The subjects of this research were students of the Arabic Language Education program at UNM. Data collection techniques were conducted through observation, tests, documentation, and questionnaires. The research data were analyzed using descriptive analysis and statistical tests to determine the effectiveness of the Quizizz application on students’ learning outcomes. The results showed that the use of the Quizizz application in Tajwid learning created a more interactive, interesting, and enjoyable learning atmosphere. Students became more active and motivated in participating in the learning process. In addition, the use of Quizizz proved to be effective in improving students’ Tajwid learning outcomes. This can be seen from the increase in students’ scores after using Quizizz compared to before its implementation. The improvement in learning outcomes occurred because students found it easier to understand the material through interactive quizzes, direct feedback, and game-based learning systems provided by Quizizz. Therefore, it can be concluded that the Quizizz application is effective as a learning medium for Tajwid among Arabic Language Education students at UNM because it can improve students’ motivation, participation, and learning outcomes.